ISOLATION OF ACTIVE COMPOUND XANTHINE OXIDASE INHIBITORS AND DEVELOPMENT OF NANOPARTICLES FROM SELECTED PLANTS OF PHYLLANTHACEAE - Husnunnisa
Hyperuricemia is the underlying cause of the inflammatory joint condition known as gout. Elevated levels of uric acid can lead to the crystallization of monosodium urate, triggering joint inflammation and diminishing the quality of life for those affected. While, uric acid can function as an antioxidant and a prooxidant, excessive levels, or hyperuricemia, tend to shift its role towards a potent oxidant effect, resulting in the deposition of uric acid crystals in the joints, thus causing gout. The xanthine oxidase enzyme emerges as a prime target for gout treatment, given its pivotal role in uric acid generation. Allopurinol, a medication commonly prescribed for gout, works by inhibiting the activity of this enzyme, thereby reducing uric acid production. However, when considering medication options, one must also weigh the potential adverse effects associated with allopurinol, such as allopurinol hypersensitivity syndrome, Stevens-Johnson syndrome, and Dress syndrome. The latter is a severe reaction characterized by skin eruptions, fever, and organ involvement. Additional adverse effects may include agranulocytosis, anemia, thrombocytopenia, leukopenia, and toxic epidermal necrolysis—a condition marked by extensive skin necrosis and peeling affecting over 30% of the body surface area, often accompanied by excruciating pain and the risk of fatality. As an alternative therapeutic approach for gout, medicinal plants from the Phyllanthaceae family present promising options. Several species within the Phyllanthus genus have long been utilized in traditional medicine to address various ailments, including excess uric acid levels, constipation, hypertension, fever, muscle aches, diarrhea, gallbladder issues, urinary tract disorders, sexually transmitted diseases, diabetes, wounds, rheumatism, and arthritis. Extracts consist of various compound components with both polar and non-polar properties, exhibiting good solubility in organic solvents but presenting challenges in dissolution in water. This difficulty in water solubility can impact the bioavailability of drugs within the body. The development of drug delivery systems seeks to address this issue by enhancing the solubility of compounds, thereby potentially increasing their pharmacological activity, particularly when administered orally. Opting for nanosuspension preparations serves the purpose of enhancing the dissolution rate of the extract, thereby potentially elevating the bioavailability of compounds that struggle to dissolve in water. Moreover, these preparations offer the advantage of delivering the compounds in liquid form, facilitating ease of administration to patients. Water, utilized as a carrier medium in nanosuspension preparations, is deemed the safest solvent for human consumption. This study was conducted in phases. Phyllanthaceae plants were screened for their best activity using in vitro tests. The inhibitory activity of the xanthine oxidase enzyme served as a guide for the subsequent standardization and isolation of active chemicals from specific plants. The next steps involved the creation of nanoparticle formulations from selected plant extracts and the evaluation of their antihyperuricemia efficacy both in vivo and in vitro. The study aimed to isolate compounds, develop extract nanoparticle formulations, and evaluate their ability to inhibit xanthine oxidase. The Phyllanthus emblica extract exhibited the highest level of xanthine oxidase enzyme inhibitory activity among the five ethanol extracts of Phyllanthaceae plants. At a concentration of 100 µg/mL, the extract showed a percentage inhibition of 56.32 ± 1.08, and at a concentration of 200 µg/mL, the percentage inhibition was 86.59 ± 0.65. Phyllanthaceae plant extract fractions were tested for xanthine oxidase inhibitory activity. The results indicated that the ethyl acetate fraction, with an IC50 value of 42.13 ± 1.16 µg/mL, had the best xanthine oxidase inhibitory activity, compared to the n-hexane fraction, air fraction, and sediment fraction. The results of the xanthine oxidase inhibition activity test of the subfraction resulting from ethyl acetate fractionation showed that the SF29A subfraction gave the best activity in inhibiting the xanthine oxidase enzyme with a % inhibition value at a concentration of 25 µg/mL of 47.81 ± 0.41 and at a concentration of 50 µg/mL of 80.10 ± 0.77. SF29A1 (rutin) and SF29A2 (quercitrin) isolates have been successfully isolated from selected plant extracts of the Phyllanthaceae family, namely Phyllanthus emblica, which are active in inhibiting the xanthine oxidase enzyme, with IC50 values of 32.77 ± 4.49 µg/mL and 23.85 ± 2.04 µg/mL, respectively. The development of the nanoparticle formula as an antihyperuricemia resulted in the preparation of an extract nanosuspension with strong inhibitory activity in vitro (IC50 value 38.37 ± 0.93 µg/mL), which outperformed the extract (IC50 value 72.55 ± 1.22 µg/mL). In in vivo testing at 60 minutes the nanosuspension extract dose of 12.5 mg/kg bw exhibited a significant difference compared to the positive control group (the group without drug administration or the test sample). The P. emblica extract exhibits antioxidant activity with an AAI DPPH value of 8.39 ± 0.04 and an AAI Cuprac of 13.19 ± 0.06, closely resembling the AAI value of the control, ascorbic acid, which has an AAI DPPH value of 10.42 ± 0.03 and an AAI Cuprac of 10.53 ± 0.03. Among the n-hexane fraction, ethyl acetate fraction, water fraction, and sediment fraction, the ethyl acetate fraction displays the best antioxidant activity, with an AAI DPPH value of 12.62 ± 0.05 and an AAI Cuprac of 23.10 ± 0.08. The antioxidant activity of isolate 1 (SF29A1) surpasses isolate 2 (SF29A2), with an AAI DPPH of 7.90 ± 0.03 and an AAI Cuprac of 15.83 ± 0.04, while the AAI DPPH of isolate 2 (SF29A2) is 3.72 ± 0.01 and the AAI Cuprac is 3.24 ± 0.03. The P. emblica extract nanosuspension preparation exhibits stronger antioxidant activity than the extract and ascorbic acid, with an AAI DPPH value of 11.15 ± 0.06 and a Cuprac AAI value of 16.11 ± 0.01. This research provides information that the P. emblica plant has the potential to be used as an alternative treatment for gout because it contains active antioxidant compounds and inhibitors of xanthine oxidase. Additionally, the development of nanosuspension preparations from this plant extract has the potential to be further developed so that they can provide benefits for individuals suffering from hyperuricemia.